Nilai Ekonomi Umbul Pengging Sebagai Area Tujuan Wisata - Sri Walyoto (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
This research was conducted to determine the consumer surplus and total economic value of the Sharia Umbul Pengging tourist destination in Dukuh Village, Banyudono District, Boyolali Regency, Central Java Province, Indonesia. The area is a natural area as a public water source managed by the local government. The main objective of this study was to analyze the demand of Umbul Pengging as a sharia tourist destination. The Travel Cost Method (TCM) is used to estimate the travel demand offered by Umbul Penggging. The evaluation approach used service preferences expressed from the point of view of the user of the Umbul Pengging dominant function. The collected data produces a tourist request function Umbul Pengging is formulated as a function of travel costs, sacrifice of travel time and income and visitor education. The results of research on travel costs, income and education of visitors are significant, tourists get benefits (surplus) for their visits.